Analisis Pengaruh Pendapatan Asli Daerah, Penanaman Modal Asing Dan Pertumbuhan Ekonomi Terhadap Indeks Pembangunan Manusia Kabupaten Mimika - Alam, Fajar Samsu; Bakar, Abu (Journal of Economics and Regional Science, 2024)
This article aims to analyze the relationship between Original Regional Income, Foreign Investment, and Economic Growth on the Human Development Index. The data used in this study is secondary data covering the period 2013-2022. The data source comes from the Central Statistics Agency. The research method applied is the Multiple linear regression Analysis method, with analysis tools using SPSS 25 software. The research results show that local income has a positive and significant effect on the human development index, while foreign investment and economic growth have a negative and significant effect on the human development index.